Nursing Perspectives in Diabetic Ketoacidosis - Pratiksha Thakare1 , Ruchira Ankar2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Diabetic ketoacidosis(DKA) is a serious life threatening condition and it occurs when insulin productionin our body is less.Diabetic ketoacidosis is a complication of diabeties mellitus and it mostly occur inhospitalize patients . Diabetic ketoacidisis condition mostly found in both type of diabeties such as Type1 and Type 2 diabeties patients. In between 20-30% of cases of diabetic ketacidosis condition occure innewly diagnosed patient with diabeties . Almost till 20 years the mortality rate of diabetic ketoacidosis is100 percent and till now there is no reduction in prevalence of diabetic ketoacidosis in younger patients dueto that children are continuous suffering with death .The mortality rate in Diabetic ketoacidosis is very important because it is a very serious life threateningcondition so the prevalence of diabeties is very crucial. The younger are the foundation of future health caredelivery system so the evaluation of their knowledge and continue development and upgrading regardingawareness and unstanding the sign and symptoms of diabetic ketoacidosis it helps to reduce the mortalityrate of Diabetic ketoacidosis.It’s an emergency condition, so the health care professional becomes a vital part of managing diabetesrelated hyperglycemic emergencies, rising health care costs and changing health care systems preventingsigns and symptoms of diabetic ketoacidosis remains an essential requirement.Effective management and prevention on diabetic ketoacidosis can reduced longer stay time in hospitalizepatient.